Sodium chloride bath - A cheap and safe tool for antiparasitic treatment of fish - J Lanikova; P Mikula; J Blahova; F Tichy; J Mares; V Enevova; L Chmelova; Z Svobodova (Veterinární Medicína, 2021)
Sodium chloride is widely used in aquaculture due to its antiparasitic effects and its ability to reduce stress during fish transport and manipulation. The aim of this study was to assess the safety of short-term exposure to sodium chloride for the common carp (Cyprinus carpio). In our experiment, fish were placed into a sodium chloride bath (c = 30 g l-1; T = 30 min; t = 20 °C) and the effects of the treatment were assessed immediately after the bath (T0) and 24, 48 and 240 h later (T24, T48 and T240, respectively), with non-treated fish serving as control groups. Though significant differences compared to the controls were observed in the treated fish sampled at T0, T24 and T48, these effects were only temporary and all the affected parameters (i.e., haemoglobin, haematocrit, plasmatic lactate, cholesterol, alanine aminotransferase, albumin, phosphorus and ceruloplasmin) had completely recovered within 10 days of exposure, suggesting that the treatment of carp with a sodium chloride bath represents a safe approach suitable for therapy of parasitic infections.